2021
DOI: 10.5325/jinfopoli.11.2021.0222
|View full text |Cite
|
Sign up to set email alerts
|

Applying a Contextual Integrity Framework to Privacy Policies for Smart Technologies

Abstract: This research anticipates a future where “smart cities” rely extensively on data analytics to determine budget allocations, to manage traffic, to design infrastructure, and to advance sustainability efforts. In this study, Helen Nissenbaum's contextual integrity framework helps us understand how smart city residents consider privacy norms, and provides a structure for comparing these norms to current data privacy practices. The study findings and policy recommendations are based on focus group discussions with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Moreover, the likely impending adoption of everyday AR pushed for by industry hastens the need for PETs that address these points. Our focus has been on giving bystanders agency over activities pertaining to them, but there are other promising routes, for example instigating privacy policies to restrict what data and activities are available at a platform level for the most important or risky contexts, such as limiting what an AR headset can do in public spaces, to mitigate against misuse and abuse of bystander data [135].…”
Section: 32mentioning
confidence: 99%
“…Moreover, the likely impending adoption of everyday AR pushed for by industry hastens the need for PETs that address these points. Our focus has been on giving bystanders agency over activities pertaining to them, but there are other promising routes, for example instigating privacy policies to restrict what data and activities are available at a platform level for the most important or risky contexts, such as limiting what an AR headset can do in public spaces, to mitigate against misuse and abuse of bystander data [135].…”
Section: 32mentioning
confidence: 99%
“…However, Lutz and Newlands (2021) measured privacy concerns around the usage of smart speakers and their survey results showed that users reported higher concerns around institutional privacy, such as concerns about contractors and third-party developers accessing personal data over those in the category of social privacy such as other household members. Adding to Lutz & Newlands’ work, a qualitative study that observed privacy attitudes on various technologies such as Ring surveillance cameras, a parking app and internet-connected water meters showed that residents noted higher concerns and mistrust for their public officials and local government agencies collecting personal information through these devices (Shaffer, 2020). Respondents of the Shaffer (2020) study vocalized overwhelming opposition to the practice of local governments collecting and selling it to third-party service providers.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Adding to Lutz & Newlands’ work, a qualitative study that observed privacy attitudes on various technologies such as Ring surveillance cameras, a parking app and internet-connected water meters showed that residents noted higher concerns and mistrust for their public officials and local government agencies collecting personal information through these devices (Shaffer, 2020). Respondents of the Shaffer (2020) study vocalized overwhelming opposition to the practice of local governments collecting and selling it to third-party service providers.…”
Section: Literature Reviewmentioning
confidence: 99%